CD8+CD28+PD1− T Cells as a Prognostic Biomarker in Endometrial Cancer - Yufei Nie; Lin Yang; Yanan Zhang; Hongyan Guo (Current Oncology)
Endometrial cancer (EC) is an immunogenic tumor, with CD8+ T cells playing a pivotal role in antitumor immunity. Overexpression of PD1 suppresses T cell function by inhibiting CD28, a critical co-stimulatory molecule. Classifying CD8+ T cells based on PD1 and CD28 expression provides valuable insights into the immune microenvironment of EC. Peripheral blood samples from 120 EC patients and tumor tissue samples from 81 EC patients were analyzed via flow cytometry. CD8+ T cells were categorized according to PD1 and CD28 expression, and their associations with clinical characteristics were systematically evaluated. Peripheral CD28−/CD8+ and PD1+/CD8+ T cell proportions were significantly associated with several high-risk factors, including deep myometrial invasion, and LVSI, as well as metabolic disorders such as dyslipidemia. Peripheral CD28+PD1−/CD8+ T cells were associated with stage, grade, and LVSI, inversely correlated with age, and elevated in patients with hypertension or dyslipidemia. Tumor-infiltrating CD28+PD1−/CD8+ T cells were associated with tumor grade and LVSI, with multivariate analysis identifying low proportions as an independent predictor of relapse. In summary, CD8+CD28− and CD8+PD1+ T cells are linked to high-risk clinical features in EC, while tumor-infiltrating CD8+CD28+PD1− T cells serve as a key independent prognostic marker for relapse. Additionally, CD8+CD28−, CD8+PD1+, and CD8+CD28+PD1− T cell proportions in PBMC are closely associated with metabolic disorders, emphasizing their potential as biomarkers for immune and metabolic interactions in EC.